Three fires - Mina, Denise (Pegasus Crime, 2023)
Reimaging the "Bonfire of the Vanities" through a series of fires lit throughout Florence at the end of the fifteenth century, this modern take on a fascinating historical story follows Girolamo Savonarola, a Dominican friar who, railing against the vice and avarice of the ruling Medici family, was instrumental in their removal from power.